Cross-Curricular Teaching and Learning in the Secondary School... Humanities: History, Geography, Religious Studies and Citizenship - Harris, Richard (Cross-curricular teaching and learning in the secondary school, 2013)
What is the role of the humanities in the modern school? Should geography, history, RE and Citizenship teachers remain faithful to long-standing subject cultures and pedagogies? Or is there another way to consider how the curriculum, and the notion of individual subjects and teachers' pedagogy, could be constructed? Drawing on case studies taken from a range of innovative secondary schools, and interrogating the use of cross-curricular approaches in UK schools, Cross-Curricular Teaching and Learning in Humanities constructs a research based pedagogy with practical steps for students and teachers as they consider how cross-curricular approaches can be implemented in their own subject areas. Key features include: Clear theoretical frameworks for cross-curricular processes of teaching and learning in the humanities Lively and engaging text that blends key issues with stories of current practice An analysis of the use of assessment, enquiry, and pupil talk as key components in building a cross-curricular approach to the humanities Practical and reflective tasks that enable to reader to apply their reading to day to day practice, alongside links to professional standards Summaries of key research linked to suggestions for further reading Professional development activities to promote cross-curricular dialogue Part of the Cross-Curricular Teaching and Learning in the Secondary School series, this timely interdisciplinary textbook is essential reading for all students on Initial Teacher Training courses and practising teachers looking to holistically introduce cross-curricular themes and practices in secondary Humanities teaching.